EFEKTIFITAS KOMBINASI EVALUASI FORMATIF DAN SUMATIF PADA PEMBELAJARAN BERBASIS PROYEK - Ririn Sri Ramadhani; Risma Handayani; Audya Pertiwi; Rismawati Rismawati; Aulia Dwina (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2023)
Learning evaluation plays an important role in ensuring the success of education, especially in project-based learning; The purpose of this study is to analyze how the combination of formative and summative evaluation can improve learning outcomes in project-based learning, as well as identify the advantages and challenges in implementing the combination of these two types of evaluation; The research method used in this study is qualitative method, this method allows the researcher to gain an in-depth understanding in combining both formative and summative evaluation in project-based learning; The results of this study reveal relevant points namely. First, formative evaluation helps learners improve the quality of the project during the process of working on the learning. Second, summative evaluation provides a comprehensive picture of students' final achievement. Third, the combination of both can improve critical thinking skills, problem solving, and concept understanding. Fourth, teachers get more accurate data to evaluate the effectiveness of learning; and contribution to the development of evaluation methods in project-based learning by understanding the effectiveness of the combination of formative and summative evaluation, teachers can optimize the learning process, create more meaningful learning experiences, and support the achievement of educational goals oriented to 21st century competencies.